Renovation priority ranking by multi-criteria assessment of architectural heritage: the case of castles - Vodopivec, Barbara; Žarnić, Roko; Tamošaitienė, Jolanta; Lazauskas, Marius; Šelih, Jana (International Journal of Strategic Property Management, 2014)
Preservation of cultural heritage is related with high costs and required interventions generally exceed available funding. It is, therefore, necessary to prioritise renovation interventions. Multi-criteria assessment can lead to scientifically sound and informed decisions about interventions. The paper presents the results of research carried out with the purpose of establishing a multi-criteria method for the assessment of architectural heritage, specifically for castles in Slovenia. It explains the methodology used to develop the multi-criteria method. Its main elements are critical content analysis of relevant literature, comparative analysis between the Slovenian and international space, and identification of relevant criteria and sub-criteria of the decision method. The course and results of empirical research, based on interviews with selected experts, is presented together with the results of the criteria importance ranking based on the Analytic Hierarchy Process (AHP) method. The research presented in this paper is interdisciplinary and brings together tangible and intangible aspects of cultural heritage. The obtained results confirm that rational determination of relative importance of individual criteria for the assessment of architectural heritage can help decision-makers to identify buildings with higher refurbishment priority. First Publish Online: 21 Mar 2014